Hand-held personal laser scanning : current status and perspectives for forest inventory application - Balenović, Ivan, inženjer šumarstva (Array, 2020)
The emergence of hand-held Personal Laser Scanning (H-PLS) systems in recent years resulted in initial research on the possibility of its application in forest inventory, primarily for the estimation of the main tree attributes (e.g. tree detection, stem position, DBH, tree height, etc.). Research knowledge acquired so far can help to direct further research and eventually include H-PLS into operational forest inventory in the future. The main aims of this review are: - to present the current state of the art for H-PLS systems - briefly describe the fundamental concept and methods for H-PLS application in forest inventory - provide an overview of the results of previous studiesÞ emphasize pros and cons for H-PLS application in forest inventory in relation to conventional field measurements and other similar laser scanning systems - highlight the main issues that should be covered by further H-PLS-based forest inventory studies.